Digital financial innovation, migration and development in sub-Saharan Africa - (:unkn) unknown (My University, 2024)
This thesis examines how digital financial innovations such as crowdfunding platforms and mobile money influence migrants’ individual and collective remittance behaviour and their impact on economic development in sub-Saharan Africa. Sub-Saharan Africa is experiencing rapid growth in the adoption of financial technologies, often in response to the inaccessibility of traditional banking services. At the same time, international migration, both intra-African and intercontinental, is playing a crucial role in the region’s economic dynamics, particularly through migrant remittances. This research is structured around three articles and adopts a mixed approach combining quantitative and qualitative analysis. The first chapter reveals that individuals who own and use a mobile money account are less likely to send funds via an informal transfer channel (friends, family, mail, Hawala, etc.). The breakdown of countries by financial development index quartile shows that the negative impact of mobile money on the use of informal channels is more pronounced in countries with an underdeveloped financial system. The second chapter highlights a positive relationship between using mobile money and establishing a non-agricultural income generating activity. The remittance channel mediates this relationship and is a function of the frequency with which remittances are received. More specifically, mobile money increases the probability of receiving remittances. However, individuals who receive remittances regularly have a lower probability of creating a non-farm income-generating activity than those who receive them less frequently. The third chapter looks at microcredit crowdfunding platforms.
Keywords: African Research